Obediencia silenciosa y negociación pragmática: Relaciones asimétricas entre prelados y mujeres consagradas en el Perú contemporáneo - Lecaros, Véronique (2025)
This article examines the relationship between the Congregation of the Sisters of St. Joseph of Tarbes and diocesan bishops in three Peruvian ecclesiastical jurisdictions. Through the cases of Piura, an unnamed diocese, and Chiclayo, the study analyzes dynamics of silent subordination and pragmatic negotiation, highlighting how women’s religious life exercises forms of empowerment within institutional tensions. Drawing from a perspective of religious anthropology, it addresses issues such as clericalism, legal vulnerability, ecclesial obedience, and the conditions for shared pastoral responsibility. These cases expose both the structural limitations faced by female religious communities and their capacity for resilience and ministerial adaptation amid synodal reforms and evolving episcopal leadership. Based on these experiences, the article proposes analytical tools to rethink the relationship between authority, charism, and women’s agency in the contemporary Catholic Church.